PELATIHAN PENGGUNAAN FITUR HEADING DAN PENGETIKAN SEPULUH JARI DI MADRASAH ALLIYAH MIFTAHUSSAADAH KOTA CIMAHI - Ernawati, Tati; Kosasih, Heldi Akbar; Rohmayani, Dini; Sugianto, Castaka Agus (PUAN INDONESIA, 2024)
The problem is that the material using the "Heading" feature on the word processor application for automatic content list creation has not been submitted.  Another problem based on the observations is that the students are still not used to typing with ten fingers so it takes a long time when practicing computers.  The method used in the implementation of training activities is to display material continued with practicum. The "Heading" feature complements the material already presented by the teacher of the TIK subject, where the material has not been presented in front of the class.  As a result of ten-finger drawing training, there was an improvement in the students' ability to type although not significantly. The training material is very relevant to the curriculum used by Madrasah Aliyah Miftahussaadah and complement the materials already learned in the learning process by the teacher of the TIK subject. The participants were very enthusiastic during the training, it is proved with the participant's activity during the receipt of the training material.  For the team especially the students give a positive impact to sharpen the softskill skills of the students before plunging into the world of work and industry as well as to society.